IMPLIKASI KLAIM TERITORIAL TURKI DAN LIBYA MELALUI MoU DELIMITASI MARITIM DI LAUT MEDITERANIA TIMUR - Putri, Naila Amalia; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Turkey's territorial claims through maritime delimitation with its neighbors are influenced by the national interests of both countries. Turkey views Libya as a neighbor and partner country that has the opportunity to avoid exclusion from its position in the Eastern Mediterranean Sea region. Maritime issues in the region have led Turkey to adopt an assertive stance in the region. The purpose of this study is to analyze the implications of Turkey and Libya's territorial claims through the MoU on maritime delimitation with Libya in the Eastern Mediterranean region. This study uses qualitative methods, with data collection techniques through document analysis sourced from several relevant and credible books, journals, articles, and websites. This study uses the Complex Interdependence Theory by Joseph Nye and Robert O. Keohane. Complex interdependence between actors or countries in achieving national interests in the region through different policies and rules has led to escalating tensions in the Eastern Mediterranean Sea region. The results of this study show several responses of rejection to the maritime delimitation MoU between Turkey and Libya internationally. Several implications of Turkey and Libya's territorial claims have arisen in relation to maritime disputes between the countries concerned and energy projects planned by regional countries without Turkey and Libya in the Eastern Mediterranean Sea, causing ongoing tensions between the countries concerned to this day. Keywords: MoU on Delimitation of the Maritime, National Interest, Eastern Mediterranean Sea.